Fabrication of carbon nanotube reinforced plastic matrix composites using 3 dimensional printing - Akpınar, Altuğ (My University, 2017)
Recently, many breakthrough manufacturing methods begin to appear. One of the most common among these methods is 3 dimensional printing which is based on additive manufacturing method. 3 dimensional printing gives us advantage of manufacturing parts in single process. Despite its advantages 3 dimensional printed products have limited mechanical properties. Due to that disadvantage, 3 dimensional printing methods are rarely used for manufacturing final products. Carbon nanotubes are carbon based nano materials which have impressive mechanical properties. In literature, there are studies about polymer matrix carbon nanotube reinforced nano composites. In those studies, it is proved that if carbon nanotubes are functionalized and dispersed adequately, polymer matrix will have greatly enhanced mechanical properties. As these superior properties of carbon nanotubes are considered, carbon nanotubes reinforced nano materials have great potential to eliminate limitation of mechanical properties of 3 dimensional printing. The aim of this study is to produce carbon nanotube reinforced resin for stereolithography type 3 dimensional printers in order to improve mechanical properties of printed products to make them available for final products. In this regard, carbon nanotubes are functionalized properly by chemical methods in order to prevent agglomeration and create viii strong interface between carbon nanotubes and polymer matrix. Carbon nanotubes are dispersed in resin homogenously by ultrasonication method. As we prepared nano composite resin, we applied sedimentation test in order to determine stability of nano composite resin. As a result of test, sedimentation was not observed in short and long term in any ratio. Subsequently we manufactured tensile and wear specimens in order to evaluate mechanical properties of nano composite specimens. As a result of mechanical tests, we observe that tensile and wear properties of 3 dimensional printed products are enhanced dramatically. As a result, we managed to prepare nano composite resin and manufactured specimens from nano composite resin. Our reinforced specimens show superior properties than base specimens. This study shows us that limited mechanical properties of 3 dimensional printed products can surpassed by using reinforcement of carbon nanotube which is processed adequately. As one of the most important problem of 3 dimensional printed products have solved, 3 dimensional printings can find itself more field of applications. Keywords: Nano composite, 3 dimensional printing, Carbon nanotube, Stereolithography, Mechanical properties.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Keywords: Nano composite; Carbon nanotube; Stereolithography